Candlelight Christmas - Wiggs, Susan (Don Mills, Ontario : MIRA Books, 2013)
As single father Logan O'Donnell prepares to give his son, Charlie, the best Christmas ever on the shores of Willow Lake, he just may be in for a Christmas surprise himself, in the form of sharp-witted and independent Darcy Fitzgerald.
Keywords: Single fathers -- Fiction; Interpersonal attraction -- Fiction; City and town life -- Fiction; Catskill Mountains (N.Y.) -- Fiction; Christmas stories